Deaeration of stable coal froth by surfactants to modify the interfacial properties. (15th August 2021) - Liu, Shiqi; Chen, Xumeng; Peng, Yongjun
Graphical abstract: Highlights: Stable coal froth could be effectively deaerated by surfactants with suitable structures. Surfactants reduced both the contact angle of particles and the air–liquid interfacial tension. The reduction of contact angle destabilised froth by detaching particles from air bubbles. The reduction of air–liquid interfacial tension had a negative effect on froth deaeration. The reduction of contact angle played a dominant role in deaerating stable froth. Abstract: Overly stable froth is an emerging problem in fuel and mineral processing plants and poses operational and safety concerns. A remedial strategy is not currently available. As a new initiative this study examined three surfactants, dioctyl sulfosuccinate sodium salt (DOSS), sodium dodecylbenzenesulfonate (SDBS) and perfluorooctanoate (PFOA) which vary in both hydrophobic chain and hydrophilic functional group, in deaerating and collapsing overly stable coal froth. The underpinning premise was that an ideal surfactant structure could modify particle surface hydrophobicity and air–liquid interfacial tension in such a way so as to destabilize stable froth. The deaeration tests together with contact angle and interfacial tension measurements indicated that the reduction of contact angle of coal particles played a dominant role in froth deaeration, while the reduction of air–liquid interfacial tension had a negative effect on destabilizing stable froth. The addition of hydrocarbon surfactants DOSS and SDBS could achieve a complete froth deaeration due to their high contents of hydrophilic polar groups and strong adsorption capacity on coal surfaces which could reduce the contact angle of coal particles to near zero. However, PFOA, a fluorocarbon surfactant, could only reduce the contact angle of coal particles moderately and therefore was not effective in deaerating stable coal froth even at a high concentration.